Unusual Presentations of Extrapulmonary Tuberculosis (Journal of Fatima Jinnah Medical University, 2018)
Objective: To describe the unusual sites of extra-pulmonary tuberculosis (EPTB) cases in a tertiary care hospital in a high burden tuberculosis country. Methodology: A cross sectional study of 100 cases was conducted at Gulab Devi Chest Hospital. All cases diagnosed and treated as EPTB (on the basis of histopathology & culture sensitivity) between January 2013 & December 2013 were included. Data was retrieved from medical records on demographics, clinical, laboratory and treatment outcome status. Results: A total of 100 patients being treated were included in the study. Mean age was 38.8 years. An overall male predominance was observed. Most common unusual presentations of EPTB by number of cases were of multiple abscesses following sinusitis and epididymitis. Conclusion: In conclusion, cutaneous tuberculosis should be included in the differential diagnosis of patients with cutaneous abscesses. Further, this study is a reminder to clinicians that extrapulmonary manifestations may serve as the initial clues to the diagnosis of M.tuberculosis infection. More population based studies should be considered to develop consensus regarding unusual presentations of EPTB.
Keywords: Mycobacteria, Multiple Abscess, Abdominal T.B, Genitourinary T.B, Prognosis.